P300 as a Potential Indicator in the Evaluation of Neurocognitive Disorders After Traumatic Brain Injury - Li, Haozhe; Li, Ningning; Xing, Yan; Zhang, Shengyu; Liu, Chao; Cai, Weixiong; Hong, Wu; Zhang, Qinting (Frontiers in Neurology, 2021)
Few objective indices can be used when evaluating neurocognitive disorders after traumatic brain injury (TBI). P300 has been widely studied in mental disorders, Cognitive dysfunction and brain injury. The daily life ability and social function are key indices in the assessment of neurocognitive disorders after TBI. The present study focused on correlation between P300 and impairment of daily living activity and social function. We enrolled 234 patients with neurocognitive disorders after TBI according to ICD-10 and 277 age and gender matched healthy volunteers. The daily living activity and social function were assessed by the social disability screening schedule (SDSS) scale, activity of daily living (ADL) scale and scale of personality change following TBI. P300 was evoked by a visual oddball paradigm. The results showed that scores of ADL scale, SDSS scale and scale of personality change in patients group were significant higher than those in control group. The amplitudes of Fz, Cz and Pz in patients group were significant lower than those in control group, and were negatively correlated with scores of ADL and SDSS scale. In conclusion, lower P300 amplitude means greater impairment of daily life ability and social function, which suggested more severity of neurocognitive disorders after TBI. P300 could be a potential indicator in evaluating the severity of neurocognitive disorders after TBI.